Investigação da atividade espasmolítica de uma série de derivados do lapachol em íleo de cobaia: um estudo comparativo - Silva, Ana Caroline de Lima (2014)
The naphthoquinones are substances of great interest, since they have a variety of biological activities. Belonging to this group, there is lapachol, an isolated naphthoquinone species of Tabebuia spp., popularly known as "ipê". Many pharmacological activities, such as spasmolytic, are related to lapachol and its natural or synthetic derivatives. Researchers have turned their attention to this molecule in order to create compounds with therapeutic potential. From this perspective it was decided to investigate the spasmolytic effect of a new series of lapachol derivatives (UFRPE 15, UFRPE 17, UFRPE 31, UFRPE 114, UFRPE 115 e UFRPE 116) and norlapachol (UFRPE 106, UFRPE 107, UFRPE 111, UFRPE 112, UFRPE 113 e UFRPE 117) in the isolated guinea pig ileum, as well as investigate the mechanism of action of the compound which show a better efficacy. In the pharmacological screening, the lapachol derivatives showed low efficacy in inhibiting the phasic contractions induced by carbachol (CCh) and histamine. Only UFRPE 115 inhibited the phasic contractions induced by histamine in a concentration-dependent manner. However, derivatives from norlapachol were more promising, since all of them inhibited the phasic contractions induced by CCh and histamine in a concentration-dependent manner, where UFRPE 107, UFRPE 112 and UFRPE 117 compounds showed a better potency and efficacy. The spasmolytic effect of these has been reported in the ileum pre-contracted with KCl, CCh or histamine, and it was noted that these three derivatives relaxed guinea pig ileum in a concentrationdependent manner, and in special the UFRPE 117 showed the highest relative potency, thus, it was selected to study its mechanism of action. Once UFRPE 117 inhibited histamine-induced contractions and relaxed the ileum pre-contracted by the same agonist, we evaluated the involvement of histamine receptors in this effect. UFRPE 117 inhibited the cumulative curves to histamine, shifting them to right and in a nonparallel manner with Emax reduction, suggesting a noncompetitive antagonism pseudo irreversible type. Since the spasmolytic potency of this compound was reduced when the ileum was pre-contracted with 40 mM KCl, we investigated the involvement of K + channels using 5 mM CsCl, a non-selective blocker of these channels, where its relaxing power was attenuated by approximately 12 folds in the presence of this blocker, suggesting the involvement of K+ channels in spasmolytic action UFRPE 117. To assess which of K+ subtypes channels were involved in this effect, we used 10-5 M glibenclamide, a KATP blocker, whose did not alter the relaxing potency of UFRPE 117, discarding the involvement of these channels. However, in the presence of 100 nM apamin, a selective blocker of SKCa and 1 mM TEA+, a selective blocker of BKCa, The UFRPE 117 relaxant potency was attenuated around 4 to 5 folds, respectively, confirming the involvement of SKCa and BKCa. Thus, the mechanism of spasmolytic action of the synthetic derivative of norlapachol, UFRPE 117, involves activation/positive modulation of SKCa and BKCa, which would lead to a hyperpolarization of the membrane, indirect blocking Cav, reduction of [Ca2+]c and consequent relaxation of this organ.